The Annotation and the Syntactic check in "Dala’el Al-Ejaz".(An inter-textual Reading ). - ناصيف ناصيف; صقر سهام; يوسف علا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research includes the annotation and the syntactic check in "Dala’el Al-Ejaz",which are the definitions identifying the composing to read the inter-textuality theory far away from the pre-planned concepts.Indeed,the concept of composing is significantly at our cultural-heritage the research is tackling at the Qura’anic miracle.While,the category has been manifested in different concepts ,revealing the intellectual perspectives and also the efficiency of the cognitive tools before the maturing phase at Al-Jurjani text which possessing the recent and the contemporary texts ,absorbing and transforming them to be settled. The composing category at "Dala’el Al-Ejaz" has several levels we choose to go deeply in the structural –syntactical level represented in Annotation and syntactic check .While, the critical inter-textuality at composing in relation to the recent and contemporary is completely another context I currently work.Therefore,the research will try to interpret at "Dala’el Al-Ejaz" Annotation and syntactic check to show the essential-implied text gradually the reading rendering and then pointing their positions at the new-text showing the transformed –strategies and how to function trying to reply the question :’’how efficiency the inter-textuality as critical interpretation reading strategy?